2022
DOI: 10.3390/jcm11082161
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Effects of Propofol and Sevoflurane Anesthesia on Optic Nerve Sheath Diameter in Robot-Assisted Laparoscopic Gynecology Surgery: A Randomized Controlled Trial

Abstract: Optic nerve sheath diameter (ONSD) is used as a surrogate parameter for intracranial pressure. This study was conducted to evaluate the effect of the anesthetics (sevoflurane and propofol) on ONSD in women undergoing robotic surgery. The 42 patients who were scheduled for robot-assisted gynecology surgery were randomly allocated to the sevoflurane group or the propofol group. ONSD was recorded at 10 min after the induction of anesthesia (T0); 5 min, 20 min, and 40 min after carbon dioxide pneumoperitoneum was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…This discrepancy is probably due to the fact that our study enrolled mostly elderly male patients, and female patients vulnerable to PONV. In Kim et al study [26] 42 female patients undergoing robot-assisted laparoscopic surgery concluded the significant increase in the ONSD of patients with a smaller ONSD increase during propofol anesthesia compared to sevoflurane anesthesia. Two patients from the Sevoflurane group experienced PONV, but this number was not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…This discrepancy is probably due to the fact that our study enrolled mostly elderly male patients, and female patients vulnerable to PONV. In Kim et al study [26] 42 female patients undergoing robot-assisted laparoscopic surgery concluded the significant increase in the ONSD of patients with a smaller ONSD increase during propofol anesthesia compared to sevoflurane anesthesia. Two patients from the Sevoflurane group experienced PONV, but this number was not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…40 min after induction of pneumoperitoneum in TP, ONSD increased significantly in the sevoflurane group compared to the propofol group. As a result, in patients undergoing robot-assisted surgery, anaesthesia with propofol produced lower increases in ONSD compared to anaesthesia with sevoflurane [ 52 ].…”
Section: Postoperative Visual Defectsmentioning
confidence: 99%
“…In recent years, many authors have investigated the role of ONSD increases in identifying how increased IOP in TP affects ICP. Many authors examined the role of Ultrasonographic measurement of ONSD in identifying ICP changes during STP, confirming that ONSD increases in TP with pneumoperitoneum, as STP and pneumoperitoneum have a detrimental effect on cerebral hemodynamic physiology [ 49 , 51 , 52 , 53 ].…”
Section: Implications For Practicementioning
confidence: 99%
“…For patients who have significant medical comorbidities, it is necessary to communicate with different medical teams to optimize their conditions, and discuss with the anesthetists on the use of anesthesia. For example, patients with hypertension, stroke or brain tumor may better receive propofol instead of sevoflurane anesthesia as the former caused less increase in ICP and optic nerve sheath diameter [60]. Special attention should be paid to patients with extreme body mass index (BMI) or big uterus and is discussed as below.…”
Section: Preventive Measures At Set-upmentioning
confidence: 99%